Rahnuma: hypergraph-based tool for metabolic pathway prediction and network comparison - Mithani, A; Preston, G; Hein, J (Oxford University Press, 2009)
We present a tool called Rahnuma for prediction and analysis of metabolic pathways and comparison of metabolic networks. Rahnuma represents metabolic networks as hypergraphs and computes all possible pathways between two or more metabolites. It provides an intuitive way to answer biological questions focusing on differences between organisms or the evolution of different species by allowing pathway-based metabolic network comparisons at an organism as well as at a phylogenetic level. Rahnuma is available online at http://portal.stats.ox.ac.uk:8080/rahnuma/.